Long term benefits of rehabilitation at home on quality of life and exercise tolerance in patients with chronic obstructive pulmonary disease. - Wijkstra, P. J. (1995)
BACKGROUND--Pulmonary rehabilitation has been shown to have short term subjective and objective benefits for patients with chronic obstructive pulmonary disease (COPD). However, appropriately controlled studies have not previously been performed, nor have the benefits of different types of continuation programme for rehabilitation been investigated. Both these problems have been addressed in a single study of the long term effects of once monthly physiotherapy versus once weekly physiotherapy at home after a comprehensive home rehabilitation programme on quality of life and exercise tolerance in patients with COPD. METHODS--Thirty six patients with severe airways obstruction (mean SD) forced expiratory volume in one second (FEV1) 1.3(0.4) 1, FEV1/inspiratory vital capacity (IVC) 37.2(7.9)%) were studied. Twenty three patients followed a rehabilitation programme at home for 18 months consisting of physiotherapy and supervision by a nurse and general practitioner. During the first three months all 23 patients visited the physiotherapist twice a week for a 0.5 hour session. Thereafter, 11 patients (group A) received a session of physiotherapy once weekly while 12 patients (group B) received a session of physiotherapy once a month. The control group C (13 patients) received no rehabilitation at all. Quality of life was assessed by the Chronic Respiratory Questionnaire, exercise tolerance by the six minute walking distance, and lung function by FEV1 and IVC. Outcome measures were assessed at baseline and at three, six, 12, and 18 months. RESULTS--Long term improvements in quality of life were found in patients in groups A and B, but not in those in group C compared with baseline, but these only reached significance in group B at all time points. Patients in group B had a higher quality of life than those in group C only at three and 12 months. There was a decrease in both six minute walking distance (at 12 and 18 months) and IVC (at three, 12, and 18 months) in patients in group C compared with the baseline measurement. Between groups analysis showed no differences for six minute walking distance, FEV1, and IVC. CONCLUSIONS--This study is the first to show that rehabilitation at home for three months followed by once monthly physiotherapy sessions improves quality of life over 18 months. The change in quality of life was not associated with a change in exercise tolerance.